Особливості застосування електросудомної терапії при наркологічній патології = Features of the application of electroconvulsive therapy in the treatment of drug abuse pathology - V. V. Chugunov; V. A. Kurilo; N. V. Danilevska (Journal of Education, Health and Sport, 2016)
Чугунов В. В., Курило В. О., Данілевська Н. В. Особливості застосування електросудомної терапії при наркологічній патології = Features of the application of electroconvulsive therapy in the treatment of drug abuse pathology Journal of Education, Health and Sport. 2016;6(9):893-901. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162962